2019
DOI: 10.48550/arxiv.1907.01766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Algorithms for Competitive Division of Chores

Abstract: We study the problem of allocating divisible bads (chores) among multiple agents with additive utilities, when money transfers are not allowed. The competitive rule is known to be the best mechanism for goods under additive utilities and was recently extended to chores by Bogomolnaia et al. [BMSY17]. For both goods and chores, the rule produces Pareto optimal and envy-free allocations. In the case of goods, the outcome of the competitive rule can be easily computed. Competitive allocations solve the Eisenberg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Nevertheless, the CE with bads exhibits far less structure than the CE with goods as explained in the introduction. There are polynomial time enumerative algorithms known only when there are constant number of agents or chores [BS19,GM20]. Quite recently, [CGMM21] gave an LCP formulation for determining CEEI with mixed manna (goods and bads) when the utility functions are separable piecewise-linear and concave (SPLC) which includes linear.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the CE with bads exhibits far less structure than the CE with goods as explained in the introduction. There are polynomial time enumerative algorithms known only when there are constant number of agents or chores [BS19,GM20]. Quite recently, [CGMM21] gave an LCP formulation for determining CEEI with mixed manna (goods and bads) when the utility functions are separable piecewise-linear and concave (SPLC) which includes linear.…”
Section: Related Workmentioning
confidence: 99%
“…Although goods and chores problems seem similar, results for chores are surprisingly contrasting: Even in the restricted case of linear disutilities, the set of CEEI can be non-convex and disconnected [BMSY17,BMSY19], and in the exchange model computing a CE is PPAD-hard [CGMM20]. No polynomial time algorithms are known to find CEEI with chores, except for when number of agents or number of chores is a constant [BS19,GM20]. 2 We note that the combinatorial approaches known for the goods case [DPSV08,Orl10,Vég12] seem to fail due to disconnectedness of the CEEI set (see Remark 1 for further explanation).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, we achieve our main result -an EF1+PO allocation of chores with bivalued utilities -using the framework of Fisher markets and competitive equilibria. Even when the items are divisible (i.e., if they can be portioned out between the agents), these remain well-defined and yield (exact) EF+PO [29]; for goods, they coincide with the maximum Nash welfare rule and can be computed in strongly polynomial time [13,27], while for chores, they have a more intricate structure [8] and their computation is an open question [10]. In case of indivisible items, Barman et al [6] use this framework to achieve EF1+PO in pseudo-polynomial time and Garg and Murhekar [18] improve the running time to polynomial when each agent has at most polynomially many utility levels across all bundles of goods.…”
Section: Related Workmentioning
confidence: 99%
“…The following property is a relaxation of EF1 and enjoys strong algorithmic support in conjunction with PO, for goods (Section 5) as well as bads (Section 7) [9,16].…”
Section: Fairness and Efficiency Propertiesmentioning
confidence: 99%
“…This is somewhat striking because it has been observed that many results for the case of goods do not easily carry over to the case of bads [14]. For example, while it is known that a competitive equilibrium with equal incomes (CEEI) fractional allocation exists for the case of bads, and such an allocation is envy-free and Pareto optimal, it is no longer obtained by maximizing or minimizing the product of (dis)utilities, and whether such an allocation can be computed in polynomial time is a major open question [16,29]. However, if such an allocation is given, Brânzei and Sandomirskiy [16] show that one can round it to obtain an integral Prop1+EF 1 1 +fPO allocation in strongly polynomial time.…”
Section: Ex-ante Ef + Ex-post Ef1 For Badsmentioning
confidence: 99%